Zależność stopy oszczędzania względem zaawansowania w cyklu życia oraz statusu społeczno-ekonomicznego - podejście wielopoziomowe - Rószkiewicz, Małgorzata (Multilevel Approach to Analysis of Social Position and Advancement in Family Life Cycle Impacting Changes in the Savings Rate of Polish Households, 2009)
The paper aimed at identifying effects of the coincidence of socio-economic status and advancement of family life cycle on the saving rate. The multilevel regression model for data from two empirical surveys was used. These results show that the socio-economic status is a crucial factor that explains variability of the saving rate, moderating its sensitivity to the demographic factors as defined in the economic theory. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 47, s. 61-69